A Study on the Mechanism of Virtual Anchors' Interactivity and Attractiveness Influencing Consumer Trust, Emotional Attitudes, and Purchase Intentions - Li Guang Yu; Wong Chee Hoo; Wei Zhi; Christian Wiradendi Wolor; Usep Suhud (Bright Publisher, 2026)
This study presents a dual-mediation model examining how the interactivity and appeal of virtual streamers affect consumers' purchase intentions. The model is anchored in the